Properties of the underwater sound fields during some well documented beaked whale mass stranding events - D'Spain, Gerald L.; D'Amico, Angela; Fromm , David M. (J. Cetacean Res. Manage., 2023)
Recent mass strandings of marine mammals, mostly Cuvier’s beaked whales (Ziphius cavirostris) from the family of ziphiidae, have occurred coincident in space and time with human production of high levels of underwater sound. Three of these events, the May 1996 mass stranding along the Greek coast, the Bahamas mass stranding event in March 2000 and the September 2002 event in the Canary Islands, were selected for consideration here since pertinent information was readily available. The purpose of this paper is to summarise the probable characteristics of the sound fields during these events and to search for common features. The acoustic sources in all three cases moved at speeds of 5 knots or greater and generated periodic sequences of high amplitude, transient pulses 15-60s apart that contained significant energy in the 1-10kHz frequency band. The environmental conditions included water depths exceeding 1km close to land. In addition, the depth dependence of the ocean sound speed created an acoustic waveguide whose lower boundary was formed by refraction within the water column. The anthropogenic sources in all cases were located within such waveguides. Under these conditions, sound levels decrease more slowly with increasing range after a certain transition range than otherwise, due to sound focusing and to decreased attenuation because of isolation over extended ranges from the ocean bottom. In addition, the frequency dispersion is such that pulses tend to remain as pulses during propagation. For those events involving near-surface sources in surface ducts, weather conditions were calm leading to minimal sound attenuation and scattering by near-surface bubbles and ocean surface roughness. Quantitative prediction of the actual sound field properties during these events is limited primarily by the lack of knowledge of prevailing environmental conditions. Results from simple numerical modelling show that received sound level increases of up to 20dB occur after the transition range for sources and receivers within refractive waveguides. Data-based semi-empirical models of surface duct propagation provide simple, realistic, quantitative estimates of the mean acoustic field in the duct and the effects of changes in environmental conditions. Numerical modelling of total sound exposure (pressure squared integrated with respect to time) illustrates the importance of the relative velocity and minimum range between source and receiver, indicating that realistic animal motion models are required to obtain representative results. Although several features of the sound fields during these three mass stranding events are very similar, their actual relationship to the strandings is unknown.